Capability–environment configurations driving exploratory innovation in art entrepreneurs: A mixed-methods configurational study - Zhaohua Chai; Na Yang (PLoS ONE, 2026)
Exploratory innovation has become a critical factor for art entrepreneurs to remain competitive in dynamic environments. However, existing studies predominantly focus on high-tech or resource-rich firms, offering limited insight into how creative entrepreneurs with constrained resources achieve such innovation. To address this gap, this study integrates dynamic capabilities theory and open systems theory to examine the complex antecedents of exploratory innovation in China’s cultural and creative industries. Based on survey data from 203 art entrepreneurs across various creative sectors, we employ a mixed-method approach combining necessary condition analysis (NCA) and fuzzy-set qualitative comparative analysis (fsQCA). The findings reveal that no single condition can be regarded as a strictly necessary condition for the outcome. Moreover, three distinct configurations lead to high levels of exploratory innovation: internally driven capability alignment, external opportunity activation, and sensing-response adaptation in the face of technological turbulence. This study contributes to the literature by extending the application of dynamic capabilities and open systems theory to the creative entrepreneurship domain and by demonstrating the methodological value of integrating NCA and fsQCA.